Trained quantity discrimination in the invasive red-eared slider and a comparison with the native stripe-necked turtle - Feng-Chun Lin; Pei-Jen Lee Shaner; Ming-Ying Hsieh; Martin J. Whiting; Si-Min Lin (Animal Cognition)
Abstract Little is known about the behavioral and cognitive traits that best predict invasion success. Evidence is mounting that cognitive performance correlates with survival and fecundity, two pivotal factors for the successful establishment of invasive populations. We assessed the quantity discrimination ability of the globally invasive red-eared slider (Trachemys scripta elegans). We further compared it to that of the native stripe-necked turtle (Mauremys sinensis), which has been previously evaluated for its superior quantity discrimination ability. Specifically, our experimental designs aimed to quantify the learning ability as numerosity pairs increased in difficulty (termed fixed numerosity tests), and the immediate response when turtles were presented with varied challenges concurrently in the same tests (termed mixed numerosity tests). Our findings reaffirm the remarkable ability of freshwater turtles to discern numerical differences as close as 9 vs 10 (ratio = 0.9), which was comparable to the stripe-necked turtle’s performance. However, the red-eared slider exhibited a moderate decrease in performance in high ratio tests, indicating a potentially enhanced cognitive capacity to adapt to novel challenges. Our experimental design is repeatable and is adaptable to a range of freshwater turtles. These findings emphasize the potential importance of cognitive research to the underlying mechanisms of successful species invasions.